Attitude of dentists about dental care of patients with special needs - Cançado Figueiredo, Márcia (2019)
Objective: Evaluate the attitude of dental surgeons (DS) in relation to dental care for patients with special needs (PSN). Methods: Transversal study that used the quantitative method through a questionnaire which was answered by 60 DS attending at Dental Conference in the state of Rio Grande do Sul, Brazil. Results: 73% of the DS do not attend this type of patients, among these: 62.1% because they do not know how to treat them; 91.4% because they did not have a Special Patients Course during their academic education; 25.9% because it requires a lot of time and patience and 69% because it needs certain emotional conditions. On the other hand, 4% of the respondents answered that they atended PSN; under some form of containment, sedation or if it was the case, refer them to a specialist. The remaining 23% of DS indicated paying attention only if they were collaborating patients. Conclusions: Dentistry for PSN in the state of Rio Grande do Sul-Brazil does not seem to satisfy the requirements of these patients, not only due to the difficulties inherent to the services and the specificities of these patients, but also of the impediments related with the dentists themselves, problems with dental techniques and all the complexity involved in caring for people with disabilities.